The Impact of Climate Change on Land Cover in Siwa Oasis as the Location of ‘Aynin Hami’ah Visited by Dh? al-Qarnayn Qur'anik - Sasongko, Wisnu; Suyadi, Suyadi; Hasyim, Abdul Wahid (Sekolah Pascasarjana Universitas Brawijaya, 2025)
In the Qur'an, Surah Al-Kahfi, there is a story of the king's journey titled Dh? al-Qarnayn, which to this day is still a mystery about who Dhulqarnayn is and the location where he travels. There is an opinion that Dh? al-Qarnayn was the King of Greece, Alexander the Great (356-323 BC), because there is a similarity in the route of travel, where Dhulqarnayn's journey to the western end (maghrib al-shams) saw the sunset in the black muddy spring of 'aynin hami?ah, and near the spring there was a settlement/qauman, where to the west of this settlement there are no more settlements, so from this point Dh? al-Qarnayn turns towards the East. This route is said to be the same as Alexander's journey to Egypt when he saw the sunset at Siwa Oasis. Near Siwa Oasis was a tribe, and to the west of the Siwa Oasis region was a vast, uninhabited Sahara desert. From this point, Alexander turned eastward. This study aims to determine the impact of Climate Change in the Siwa Oasis area against land cover change. The method used compared climate variable data from 1984-2020 and the comparison of land cover area from satellite images in 1984, 2002, and 2020. The results of this study stated that there was climate change and land cover change in Siwa Oasis. Still, climate change did not have an impact on macro land cover, namely the thematic change of land cover type, where the remains of black muddy springs 'aynin hami?ah in Siwa Oasis are still visible, and there are still settlements/qauman on the banks of the Oasis of Siwa, and to the west of the oasis is still the Sahara Desert, a vast uninhabited area. Keywords: 'aynin hami?ah, Climate Change, Dh? al-Qarnayn, Landcover, Siwa Oasis